Peripartum hysterectomy: prospective observational study in a tertiary care centre of north India - Masuma Rizvi, Syed; Shah, Zeenat U.; Farooq, Sofia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Emergency peripartum hysterectomy is a vital surgical procedure performed at the time of vaginal or caesarean delivery or in the immediate postpartum period in cases of intractable postpartum haemorrhage unresponsive to other conservative measures. Such hemorrhage may be due to atonic uterus, uterine trauma, coagulation disorders, abnormal placentation, not treatable by conservative measures. Methods: This study was conducted for a time period of 1.5 years from March 2016 to September 2017, in the department of Obstetrics and Gynecology, GMC Srinagar, Jammu and Kashmir, India. All such patients in our hospital were included in this study. The incidence, risk factors, age, parity, gestational age, indications for performing hystrectomy, pre and post-operative complications were studied. Results: The incidence was 3.2/1000 deliveries. The average age of the patients in our study was 31.18±2.80 years. Most patients were delivered at gestation of 37-38 weeks (61.17%). Among the patients undergoing peripartum hysterectomy 87.38% had caesarean delivery and 12.62% had vaginal delivery. The commonest indication of peripartum hystrectomy in our study was abnormal placentation (67.96%) with accreta accounting for most of these cases (53.40%). Conclusions: The incidence of peripartum hystrectomy in our centre has increased with time, which can be accounted by increase in the rate of caesarean sections over time which has led to the emergence of morbidly adherent placentation as the commonest risk factor for peripartum hysterectomy.